Remembering the First World War
1 online resource (xiv, 253 pages)
Keywords: "Discusses how and why the First World War is remembered, looking at family history, practices of remembering through film, literature, monuments and museums, and public rituals of remembrance throughout the world"--Provided by the publisher.